2020
DOI: 10.1002/acm2.13128
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of adaptive intensity‐modulated proton therapy in nasopharyngeal carcinomas

Abstract: Purpose: To investigate potential advantages of adaptive intensity-modulated proton beam therapy (A-IMPT) by comparing it to adaptive intensity-modulated X-ray therapy (A-IMXT) for nasopharyngeal carcinomas (NPC).Methods: Ten patients with NPC treated with A-IMXT (step and shoot approach) and concomitant chemotherapy between 2014 and 2016 were selected. In the actual treatment, 46 Gy in 23 fractions (46Gy/23Fx.) was prescribed using the initial plan and 24Gy/12Fx was prescribed using an adapted plan thereafter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…All recurrences were observed in the high dose region [ 12 ]. Minatogawa et al compared the results of adaptive IMRT with adaptive IMPT and showed a statistically significant reduction in the of the right parotid gland, both temporomandibular joints, the oral cavity, the larynx (all with ) and thyroid gland ( ) when using adaptive IMPT [ 18 ]. The retrospective study by Placidi et al reported about plan adaptations in 5.5% of the studied cases, which were treated with PBS, as a result of anatomical changes during the PT course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All recurrences were observed in the high dose region [ 12 ]. Minatogawa et al compared the results of adaptive IMRT with adaptive IMPT and showed a statistically significant reduction in the of the right parotid gland, both temporomandibular joints, the oral cavity, the larynx (all with ) and thyroid gland ( ) when using adaptive IMPT [ 18 ]. The retrospective study by Placidi et al reported about plan adaptations in 5.5% of the studied cases, which were treated with PBS, as a result of anatomical changes during the PT course.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the need for adaptive proton therapy (APT) planning needs to be evaluated. Previous studies pointed out the need to account for anatomical changes during the course of RT [ 10 , 12 , 13 , 14 ] and particularly PT treatment [ 15 , 16 , 17 , 18 ], especially for tumors of the head and neck. There is clearly less corresponding evidence for PT of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key role played by RT has been recently strengthened by the introduction of proton therapy (PT) as a RT treatment option for head and neck cancer (HNC), including NPC [ 8 ]. In particular, intensity-modulated proton therapy (IMPT) has the possibility to reduce radiation-induced side-effects to organs-at-risk (OARs) while guaranteeing highly conformal coverage of the target compared to advanced photon-based RT techniques, such as volumetric modulated arc therapy (VMAT) [ 9 ]. Planned comparison studies between IMPT and IMRT techniques have suggested that lower (mean) doses can be delivered to several organs at risk (OARs) in patients with NPC [ 10 , 11 , 12 , 13 ], without significant difference in target coverage, conformity, or homogeneity indexes [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a predictive replan approach can offer advantages in improving clinical workflow efficiency. Intensity modulated proton therapy (IMPT) offers the potential to limit dose to normal tissues for head and neck (H&N) cancer patients [1][2][3][4][5]. However, this precise delivery technique has inherent sensitivity to uncertainties.…”
Section: Introductionmentioning
confidence: 99%